Contemporary Japanese cinema since Hana-bi - Bingham, Adam (Edinburgh Edinburgh University Press, 2015)
"Yakuza, samurai and horror films have been some of the most popular genres in Japanese cinema over the last two decades, with a clearly defined generic lineage in the country's cinematic tradition. Studying these and other genres through a close analysis of their most representative films, this innovative study examines the way individual films have either adapted to or drawn away from their own genre conventions, or, in the case of 'magic realist' films, have introduced significant new developments which have little real precedent in Japanese filmmaking. With close textual analysis, this study looks at the prevalence of repetition and variation in these contemporary Japanese genres, offering for the first time in English an academic appreciation and overview of popular Japanese cinema in the new millennium. Look at the work of directors as varied as Kitano 'Beat' Takeshi and Kurosawa Kiyoshi, and films as iconic as Hana-Bi and The Bird People in China, this book provides an invaluable resource for film students and scholars alike."--Back cover.
Introduction: Why 1997 and Hana-Bi? -- 1. Jidai-geki and Chambara: the samurai onscreen -- 2. Yakuza cinema -- 3. Japanese horror cinema -- 4. The changing Japanese family on film -- 5. Postmodernism and magic realism in contemporary Japanese cinema -- 6. Japanese documentary cinema: reality and its discontents -- 7. Modern Japanese female directors.
Includes bibliographical references (pages 203-213), filmography, and index.
Keywords: Kitano -- Takeshi -- 1947-.; Kurosawa -- Kiyoshi -- 1955-.; Miike -- Takashi -- 1960-.; Motion pictures -- Japan -- History; Motion pictures; Japan